2021
DOI: 10.1111/bjh.17615
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of lymphocyte‐variant hypereosinophilic syndrome (L‐HES): what to consider after confirming the elusive diagnosis

Abstract: Lymphocyte-variant hypereosinophilic syndrome (L-HES) is a rare disease driven by immunophenotypically aberrant T cells producing eosinophilopoetic cytokines such as interleukin-5 (IL-5). Treatment is challenging because L-HES is relatively steroid resistant and not amenable to tyrosine kinase inhibitors. We searched the literature for clinical trials and observational studies, including case reports, of patients treated for L-HES. In all, 25 studies were selected; two were randomised controlled trials of IL-5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 64 publications
0
7
0
Order By: Relevance
“…However, work-up for additional secondary causes of eosinophilia, such as L-HES, IgG4-RD and EGPA, received little attention from clinicians. A combination of bone marrow biopsy, cytogenetics, flow cytometry immunophenotypic analysis and T-cell clonality studies are necessary to determine the diagnosis of L‐HES [ 9 ]. When IgG4-related disease is suspected, serum protein electrophoresis (SPEP) and IgG subclasses are helpful as initial tests [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, work-up for additional secondary causes of eosinophilia, such as L-HES, IgG4-RD and EGPA, received little attention from clinicians. A combination of bone marrow biopsy, cytogenetics, flow cytometry immunophenotypic analysis and T-cell clonality studies are necessary to determine the diagnosis of L‐HES [ 9 ]. When IgG4-related disease is suspected, serum protein electrophoresis (SPEP) and IgG subclasses are helpful as initial tests [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…A variety of causes of eosinophilia have been widely recognized including asthma, dermatosis diseases, hematological malignancy, drug‐effect, parasitic infections, gastrointestinal disorders and vasculitides [ 6 , 7 ]. Recently, an increasing number of studies demonstrated that lymphocyte variant of HES subtype (L-HES), Immunoglobulin G4-related disease (IgG4-RD) and Eosinophilic granulomatosis with polyangiitis (EGPA) could be the common causes of secondary eosinophilia [ 8 , 9 ], but with inadequate evaluation. Patients with eosinophilia could exhibit with different symptoms involving multiple organs, which could be neglected by clinicians easily [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] The liver remains the target that can be damaged by hepatitis B and C. According to the World Health Organization (WHO, 2019), hepatitis affects around 325 million people globally, with viral hepatitis B and C causing approximately 1.4 million fatalities each year. [4,5] Hepatitis is the second leading cause of death in the world. People are 9 times more likely to get hepatitis than they are to contract HIV after tuberculosis.…”
Section: Introductionmentioning
confidence: 99%
“…Treatment of L‐HES is different from other types of HE, so it is important to distinguish. The standard treatment for L‐HES is steroids and/or pegylated interferon alpha 10,11 . Steroids, used primarily for HE, can be considered first‐line treatment for L‐HES, but are relatively steroid‐resistant and less responsive than other types of HES.…”
Section: Introductionmentioning
confidence: 99%
“…The standard treatment for L-HES is steroids and/or pegylated interferon alpha. 10,11 Steroids, used primarily for HE, can be considered first-line treatment for L-HES, but are relatively steroid-resistant and less responsive than other types of HES. Although there are further clinical trials are needed, there are many available treatments options for L-HES, including interferon-alpha (IFN-α), anti-IL-5 monoclonal antibodies, cyclosporine, and mycophenolic acid.…”
mentioning
confidence: 99%